Is audio computer-assisted self-interview (ACASI) useful in risk behaviour assessment of female and male sex workers, Mombasa, Kenya? - van der Elst, E; Okuku, H; Nakamya, P; Muhaari, A; Davies, A; McClelland, R; Price, M; Smith, A; Graham, S; Sanders, E (Public Library of Science, 2009)
BACKGROUND: Audio computer-assisted self-interview (ACASI) may elicit more frequent reporting of socially sensitive behaviours than face-to-face (FtF)-interview. However, no study compared responses to both methods in female and male sex workers (FSW; MSW) in Africa. METHODOLOGY/PRINCIPAL FINDINGS: We sequentially enrolled adults recruited for an HIV-1 intervention trial into a comparative study of ACASI and FtF-interview, in a clinic near Mombasa, Kenya. Feasibility and acceptability of ACASI, and a comparative analysis of enrolment responses between ACASI and FtF on an identical risk assessment questionnaire were evaluated. In total, 139 women and 259 men, 81% of eligible cohort participants, completed both interviews. ACASI captured a higher median number of regular (2 vs. 1, p<0.001, both genders) and casual partners in the last week (3 vs. 2, p = 0.04 in women; 2 vs. 1, p<0.001 in men). Group sex (21.6 vs. 13.5%, p<0.001, in men), intravenous drug use (IDU; 10.8 vs. 2.3%, p<0.001 in men; 4.4 vs. 0%, p = 0.03 in women), and rape (8.9 vs. 3.9%, p = 0.002, in men) were reported more frequently in ACASI. A surprisingly high number of women reported in ACASI that they had paid for sex (49.3 vs. 5.8%, p<0.001). Behaviours for recruitment (i.e. anal sex, sex work, sex between males) were reported less frequently in ACASI. The majority of women (79.2%) and men (69.7%) felt that answers given in ACASI were more honest. Volunteers who were not able to take ACASI (84 men, and 37 women) mostly lacked reading skills. CONCLUSIONS/SIGNIFICANCE: About 1 in 5 cohort participants was not able to complete ACASI, mostly for lack of reading skills. Participants who completed ACASI were more likely to report IDU, rape, group sex, and payment for sex by women than when asked in FtF interview. ACASI appears to be a useful tool for high risk behaviour assessments in the African context.